2018
DOI: 10.2355/isijinternational.isijint-2018-044
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Evaluation of Corrosion Resistance of Trivalent Chromate Conversion Coatings with Different Organic Additives

Abstract: The corrosion resistance of electrogalvanized steels with trivalent chromate conversion coatings is investigated electrochemically to analyze the effect of organic additives on the corrosion resistance under wet-dry cyclic conditions. Three sets of polyamine additives, namely (i) imidazole and epihalohydrin, (ii) polyquaternary amine salt, and (iii) polyethyleneimine, are examined and compared. Electrochemical impedance spectroscopy and anodic stripping were employed to evaluate the corrosion resistance. Cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Some prior works have pointed to deposition conditions, including current density, plating bath formulation, and plating duration as factors influencing the morphology developments of electrogalvanized deposits [ 11 , 26 , 27 ]. Surface morphology of zinc coatings is found to play an important role controlling their corrosion properties [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some prior works have pointed to deposition conditions, including current density, plating bath formulation, and plating duration as factors influencing the morphology developments of electrogalvanized deposits [ 11 , 26 , 27 ]. Surface morphology of zinc coatings is found to play an important role controlling their corrosion properties [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Opuntia streptacantha cactus, native to central Mexico, was used in this study. Cladodes aged between 2 and 3 years were considered since they contain the highest concentrations of mucilage, according to previous studies [29]. Mucilage extraction was performed according to Sepúlveda et al [30].…”
Section: Obtaining Mucilage Treatment Of Cochineal and Formulation Of...mentioning
confidence: 99%
“…The conventional approach to improve the corrosion resistance of ZnNi coating is to fabricate the topcoat as conversion coating (trivalent chromate conversion coating [CCC]). The trivalent CCC has been used widely to passivate zinc alloys (Osborne, 2001) and zinc-coated steel (Wanotayan et al , 2018; Huong et al , 2019a). In the previous work by salt spray test (Huong et al , 2019a), we observed the appearance of white rust after 1 h and 400 h for Zn/steel and CCC/Zn/steel samples, respectively.…”
Section: Introductionmentioning
confidence: 99%